Effects of gravitational stresses on mitral valve prolapse. I. Changes in auscultatory findings produced by progressive passive head-up tilt. Issue 5 (May 1978) - Towne, W D; Patel, R; Cruz, J; Kramer, N; Chawla, K K
Abstract : The effects of passive head-up tilt on systolic time intervals were assessed in 18 patients with mitral valve prolapse. In addition to causing prolongation of the pre-ejection period and shortening of left ventricular ejection time, this circulatory stress led to progressive shortening of the Q to click interval. In 1 patient, a systolic click became audible which had not been heard in the supine posture. In 7 patients the click disappeared during head-up tilt, usually at 60 degrees or 90 degrees. In 2 patients without a murmur while supine, a mid-late systolic murmur appeared with tilt; 1 of these 2 as well as another patient who had a soft late systolic murmur while supine developed loud systolic whoops at greater angles of tile. The correlations between Q to click interval and aortic valve opening to click interval, and both the angle and the sine of the angle of tilt were highly significant.